Genetic diversity of Panax vietnamensis var. fuscidiscus K. Komatsu, s. Zhu & S.Q. cai population in western north of vietnam detected by inter simple sequence repeat markers - Lê, Ngọc Triệu (Vietnam, 2022)
Panax vietnamensis var. fuscidiscus is a previous medicinal plant which was recently discovered in Sin Ho and Muong Te district, Lai Chau province of Vietnam. In this study, inter simple sequence repeat (ISSR) markers were employed to investigate the genetic diversity and variability of 46 individuals belonging to a naturally distributed population of this variety in Vietnam. Genetic diversity at the population level was high (He = 0.2298, I = 0.3634 and PPB = 96.99%). The group of mature individuals possessed the higher genetic diversity (HeO = 0.229, IO = 0.3563 and PPBO = 84.34%) as compared to group of young individuals (HeY = 0.2086, Iy = 0.3291 and PPBY = 83.74%). The intergroup gene differentiation was high (GST = 0.0499) with the genetic distance among groups was D = 0.0298. The similarity coefficient among mature individuals was more moderate (Maximum = 0.873, Minimum = 0.614 and Average = 0.741) than among young individuals (Maximum = 0.916, Minimum = 0.596 and Average = 0.759). Results on genetic diversity and variability showed that the investigated population has coped with the risk of decline and needed to be protected